The influence of cultural similarity and individual factors on visitation - Ng, Siew Imm; Lee, Julie Anne; Soutar, Geoffrey N. (Tourism Educators Association of Malaysia, 2009)
This paper examined how Chinese, German and American individuals’ perceptions of cultural similarity/difference influence intentions to travel to New Zealand, a novel long-haul destination. The relationship was examined along with a set of potentially influential individual difference variables, including international travel experience, uncertainty avoidance, novelty seeking and ethnocentrism. Cultural similarity was a common positive predictor of travel intentions toward New Zealand across all three countries. Respondent’s travel experience and novelty seeking were also important positive influences for this long-haul destination, at least for Americans and Germans. Respondent’s level of uncertainty avoidance was only significant for Germany, where those with higher uncertainty were less likely to intend to visit New Zealand. Ethnocentrism was not a significant predictor in any country. These findings suggest that the perception of cultural similarity, which can be influenced by marketing campaigns, has a positive influence on travel intentions. Tourism marketers should stress elements of cultural similarity in their campaigns, especially for those markets where there may be lower levels of knowledge about the destination.